El museo sin musas. Nuevas coordenadas para una museología posthumana en el siglo XXI - Óscar Navajas Corral (Midas: Museus e Estudos Interdisciplinares)
In the 3rd century BC Alexandria named the abode of the Muses: the Mouseion. From that moment until today the Temple of the Muses has been an essential pillar in our societies. Not for this reason, we have stopped criticizing it, deconstructing it and removing it from its strong and sacrosanct walls to expand it to the territory and to the entire society. We have constantly modified its coordinates, especially in the museological revolution that occurred with the New Museology in the second half of the 20th century. In the museum the social began to take precedence, they became humanized. The object and objective of the institution now were people and their needs and social problems. In the first quarter of the 21st century, museums continue to change their coordinates. Now, under the umbrella of the so-called Social Museology, they are asked to face new challenges: social justice, subalternity, decolonization, sustainability, etc. In this article, from a historiographical methodology and the postulates of posthumanism, we intend to trace this evolution and indicate how the social vision of museology is capable of promoting a more human museum, which can meet the challenges of this millennium.